PEMANFAATAN SLUDGE HASIL PENGOLAHAN LIMBAH CAIR PT. INDOFOOD CBP DENGAN PENAMBAHAN SAMPAH DOMESTIK SERTA EFFECTIVE MICROORGANISM (EM4) DAN LUMPUR AKTIF SEBAGAI AKTIVATOR MELALUI PROSES PENGOMPOSAN - Anitia Arumsari Arumsari (Jurnal Teknik Lingkungan, 2012)
This research uses a sludge of waste from IPAL PT. Indofood CBP Semarang as raw material compost in composting process. The composting process was conducted in 28 days by an aerobic condition with 8 variations of compost. In this experiment, rubbish were added as mixed material; and we were also added effective microorganism (EM4) and some activated sludge as activator in order to accelerate in composting process. The result showed that quality of compost from sludge waste has been following the standard quality of SNI 19-7030-2004, but the pH of variation control by adding EM4 and a content of moisture in variation A2, B2 and control with activated sludge are not appropriate. From this research, the quality of matured compost with the addition of EM4 and activated sludge as activator were not significantly different. The best compost subsist on variations C1 with proportion of sludge and rubbish is 10:1 and additional aktivator of EM4 with the result (C-organic= 10,13%; N= 0,74%; ratio C/N = 13,66; P= 0,51%; K= 0.45%; moisture= 42,68 % ).